2011
DOI: 10.1007/s11238-010-9240-5
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Condorcet: optimal aggregation rules using voting records

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…were the 'correct' ones, we can determine, for any individual voter and to high precision, how likely he is to choose correctly this time around. We do so through a process called 'Q', developed by Baharad et al (2011Baharad et al ( , 2012 We would seem justified in taking a dim view of Smith's competence as a result of what we know about his choice in the first election and that election's overall result. There is, ex hypothesi, a truth of the matter about whether A or B is correct, and Smith's judgement was contradicted by the independent judgements of 120 million other people.…”
Section: The Application Of Theory To Politicsmentioning
confidence: 99%
“…were the 'correct' ones, we can determine, for any individual voter and to high precision, how likely he is to choose correctly this time around. We do so through a process called 'Q', developed by Baharad et al (2011Baharad et al ( , 2012 We would seem justified in taking a dim view of Smith's competence as a result of what we know about his choice in the first election and that election's overall result. There is, ex hypothesi, a truth of the matter about whether A or B is correct, and Smith's judgement was contradicted by the independent judgements of 120 million other people.…”
Section: The Application Of Theory To Politicsmentioning
confidence: 99%
“…There are various ways to model partial knowledge of expert competences (Baharad et al, 2011(Baharad et al, , 2012. Perhaps the simplest scenario for estimating the p i s is to assume that the i th expert has been queried independently m i times, out of which he gave the correct prediction k i times.…”
Section: Unknown Competences: Frequentist Approachmentioning
confidence: 99%
“…For a binary-choice problem with one correct and one wrong choice, the law of large numbers has mathematically explained the reason behind the higher accuracy of a majority vote compared to an individual's decision-making [2,[16][17][18][19][20]. Theoretical studies have also revealed that the optimum weight to be given to opinions to maximise the majority vote accuracy is proportional to the log-odds ratio of the individual's ability [17,18,21].…”
Section: Introductionmentioning
confidence: 99%